Analyzing the Socio-economic Condition of the Urban Poor at West Bakalia, Chittagong (Journal of Bangladesh Institute of Planners, 2018)
Chittagong city dwellers face the consequences of inadequately planned and managed urbanization as the city is unable to provide proper services and facilities to all classes of people. West Bakalia area is a deprived part of the Chittagong city located near the Karnafuli river. One of the main canals of the city ‘Chaktai khal’ and its branches passes through it. Questionnaire survey and focus group discussion are conducted to understand the nature of this problem. Multidimensional Poverty Index (MPI) method is used to identify the poverty level of the people in West Bakalia. Participatory Rural Approach (PRA) method is used to seek out the causes and effects of the poor’s socio-economic condition with cause-effect diagram tool, mobility pattern showing frequency, mode choice and destination of the respondents with mobility map, social institutions and resources of the area with social and resource map. They suffer from poor road surface condition, poor accessibility and safety issues too. Also, unavailability of healthcare center facility and recreational places has worsened the situation in the area with poor livable condition. The urban poor and their right to have livable condition must be accepted as an important factor and therefore included in the more appropriate planning framework for Chittagong city following the recommendations provided in this research.JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 125-135